Kajian Semiotika Lagu Timur 2025 Sebagai Bahan Pembelajaran Bahasa Indonesia dalam Kurikulum Merdeka - Selvi Nurul Hidayati; Aditya Ansor Alsunah; Lina Siti Nurwahidah; Cecep Dudung Julianto (Asosiasi Ide Bahasa Kepri, 2025)
This study analyzes the layers of meaning in song lyrics using Roland Barthes’ semiotic framework, which includes denotation, connotation, and myth. The research aims to reveal how linguistic signs in the lyrics function as cultural representations reflecting identity, emotional expression, and social narratives. A qualitative descriptive method was employed by examining textual signs, connotative associations, and cultural myths embedded in the song. The findings indicate that the lyrics convey not only literal meanings but also symbolic meanings shaped by local cultural contexts. At the denotative level, the lyrics present explicit narrative elements, while at the connotative level, figurative language and cultural references reveal deeper emotional and ideological meanings, and at the myth level, the song reproduces collective values, cultural identity, and social worldviews. Furthermore, the analysis shows that song lyrics are relevant to be utilized as learning materials in Indonesian language education within the implementation of the Merdeka Curriculum, as they support contextual learning, literacy development, critical thinking skills, and students’ cultural awareness. Overall, Barthes’ semiotic approach proves effective in uncovering the symbolic and socio-cultural meanings of song lyrics.